Meningkatkan Kemampuan Representasi Matematika Siswa Melalui Penerapan Model Pembelajaran Novick - Sri Rezeki (Universitas Indraprasta PGRI Jakarta, 2017)
This research aims to study the improvement in mathematical representation ability of the students through the application of Novick learning model. The population of this research is all students of class X in one of private Senior High Schools (SMA) in Bandung, with two classes taken as the sample. The experimental class is taught using Novick learning model while the control class is taught employing a conventional learning model. Sampling is conducted adopting a purposive sampling technique. The data analysis is quantitatively performed by analyzing the pre-test and the average N-gain data between the two sample groups by using Games-Howell test and two-way ANOVA test. The result of the research shows an improvement in the mathematical representation ability of students learning with Novick learning model is better than those learning with a conventional learning model.